Development of a Dusky kob scFv gene phage display library for the discovery of antibodies to Brome mosaic virus - a proxy for a novel, emerging fish pathogen - Naylor, Kyle Andrew (Department of Molecular and Cell Biology, 2022)
Fish farming is rapidly becoming the world's fastest growing production sector, achieving an annual growth rate of approximately 8.9% since the early 1970s. However, high stocking densities result in elevated stress levels in farmed fish, leading to increased susceptibility to infection by opportunistic pathogens and parasites. Antibody phage display is a method that allows foreign peptides or proteins to be expressed on the phage surface through translational fusion with phage coat proteins. Consequently, antibodies expressed by a diverse repertoire of genes coding for the single chain variable fragment (scFv) of immunoglobulin M can be isolated and screened for affinity to a specific infectious agent or parasite. In this study, a phage display library displaying scFvs derived from combination pairings of Dusky kob (Argyrosomus japonicas) variable heavy and light chain fragments, sourced from the splenic B cells of healthy Dusky kob, was constructed. The library was subjected to two rounds of biopanning against brome mosaic virus (BMV), a grass virus to which Dusky kob would have no prior exposure that served as a proxy for an emerging fish pathogen. Five clones were identified as having high affinity and specificity to BMV, as determined by phage enzymelinked immunosorbent assay (ELISA) and phage western blot analysis, respectively. To validate the diagnostic and therapeutic potential of antibody fragments isolated from this phage display library, the gene encoding the antibody fragment of the clone displaying the highest affinity to BMV was selected and expressed using a yeast surface display system. ELISA analysis of serum sampled from Dusky kob exposed to BMV by injection demonstrated that the yeast displayed anti-BMV antibody could successfully detect BMV in the blood serum of BMV-infected Dusky kob with similar sensitivity to a commercially available counterpart. Similarly, this study demonstrated the neutralising effect of yeast displayed anti-BMV antibodies which were found to successfully reduce BMV infection in barley. Overall, these findings demonstrate the feasibility of a Dusky kob phage display library as a source of diagnostically and therapeutically important antibodies against emerging fish pathogens or parasites that threaten the fish farming industry of South Africa.